Orthography of Ta' Marbuthah and Ta' Mafthuhah in the Qur'an - Manoppo, Ningsi; Abdullah, Abdullah (Language Development Center, 2024)
Background: The writing of the Qur'an often involved the use of two forms of the letter ta', namely Ta' Marbuthah and Ta' Maftuhah. Inconsistencies in this writing, according to the rasm Usmani, raised the need for a deeper understanding of its writing rules. Purpose: This article aimed to discuss the writing of Ta' Marbuthah and Ta' Maftuhah in the Qur'an, evaluating its orthographic rules and implications. Method: This research employed a qualitative approach with descriptive analysis of the Qur'anic text and related literature on Arabic orthography. Primary sources included both classical and modern works that discussed rasm Usmani. Results and Discussion: It was found that Ta' Marbuthah was generally used at the end of words indicating feminine gender or mu'annats, while Ta' Maftuhah was more often found in words with endings that did not necessarily indicate mu'annats. Additionally, in some contexts, words that conformed to general Arabic writing rules still used different forms in rasm Usmani. Conclusions and Implications: A correct understanding of the writing rules of Ta' Marbuthah and Ta' Maftuhah was crucial to maintaining consistency and accuracy in the writing of the Qur'an. This also helped in understanding the proper meaning and pronunciation according to rasm Usmani.